Constitutionalism and dictatorship : Pinochet, the Junta, and the 1980 constitution - Barros, Robert, 1957- (Cambridge studies in the theory of democracy., 2002)
"It is widely believed that autocratic regimes cannot limit their powers through institutions of their own making. This book presents a surprising challenge to this view. It demonstrates that the Chilean armed forces were constrained by institutions of their own design. Based on extensive documentation of military decision making, much of it long classified and previously unavailable, this book reconstructs the politics of institutions within the recent Chilean dictatorship (1973-1990)